Pregnancy dating by fetal crown–rump length: a systematic review of charts. (6th January 2014) - Napolitano, R; Dhami, J; Ohuma, EO; Ioannou, C; Conde‐Agudelo, A; Kennedy, SH; Villar, J; Papageorghiou, AT
<x xml:space="preserve">Abstract</x> Background Fetal crown–rump length (CRL) measurement by ultrasound in the first trimester is the standard method for pregnancy dating; however, a multitude of CRL equations to estimate gestational age (GA) are reported in the literature. Objective To evaluate the methodological quality used in studies reporting CRL equations to estimate GA using a set of predefined criteria. Search strategy Searches of MEDLINE, EMBASE, and CINAHL databases, from 1948 to 31 January 2011, and secondary reference sources, were performed. Selection criteria Observational ultrasound studies, where the primary aim was to create equations for GA estimation using a CRL measurement. Data collection and analysis Included studies were scored against predefined independently agreed methodological criteria: an overall quality score was calculated for each study. Main results The searches yielded 1142 citations. Two reviewers screened the papers and independently assessed the full‐text versions of 29 eligible studies. The highest potential for bias was noted in inclusion and exclusion criteria, and in maternal demographic characteristics. No studies had systematic ultrasound quality‐control measures. The four studies with the highest scores (lowest risk of bias) satisfied 18 or more of the 29 criteria; these showed lower variation in GA estimation than the remaining, lower‐scoring studies. This was particularly evident at the extremes of GA. Author's conclusions Considerable methodological heterogeneity and limitations exist in studies reporting CRL equations for estimating GA, and these result in a wide range of estimated GAs for any given CRL; however, when studies with the highest methodological quality are used, this range is reduced.